Growth evolution of ZnO thin films deposited by RF magnetron sputtering - Rosa, A. M. [UNESP]; Silva, E. P. da [UNESP]; Amorim, E. [UNESP]; Chaves, M. [UNESP]; Catto, A. C.; Lisboa Filho, Paulo Noronha [UNESP]; Bortoleto, J. R. R. [UNESP] (Iop Publishing Ltd, 2012)
We study the surface morphology evolution of ZnO thin films grown on glass substrates as a function of thickness by RF magnetron sputtering technique. The surface topography of the samples is measured by atomic force microscopy (AFM). All AFM images of the films are analyzed using scaling concepts. The results show that the surface morphology is initially formed by a small grains structure. The grains increase in size and height with growth time resulting in the formation of a mounds-like structure. The growth exponent, beta, and the exponent defining the evolution of the characteristic wavelength of the surface, p, amounted to beta = 0.76 +/- 0.08 and p = 0.3 +/- 0.05. From these exponents, the surface morphology is determined by the nonlocal shadowing effects, that is the dominant mechanism, due to the incident deposition particles during film growth.